Pengembangan Media Pembelajaran Pengenalan Makanan Sehat Augmented Reality Bagi Anak Sekolah Dasar Kelas 1 - Al Zahro, Sabrina; Antoni, Ferdi; Ratnawati, Dwi (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
This research was developed to overcome the problem of young children who find it very difficult to understand learning about healthy food in a monotonous way. When playing alone when the teacher gives an explanation is a sign that the child is bored with the learning activity. Early childhood children tend to obey their teachers more than their parents. This research aims to develop Augmented Reality learning media for the introduction of healthy food for grade 1 elementary school children using the Research and Development (R&D) method. The result of this development and research is an Augmented Reality Learning Media Application for Introduction to Healthy Food for grade 1 Elementary School children. The development of learning media in this research has been tested with several experts consisting of media experts, material experts and respondents. The test results from this research reached 87%, which means this application can be categorized as very suitable for use. Based on the tests that have been carried out, it can be concluded that this research and development has produced a product in the form of a learning media application for the introduction of healthy food which is very suitable for use by grade 1 Elementary School children.